A Comprehensive Review of Tubulointerstitial Nephritis and Uveitis (TINU) Syndrome - Alexandra Bograd; Arnd Heiligenhaus; Stefan Reuter; Christoph Tappeiner (Biomedicines)
Background: Tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare autoimmune disorder, characterized by acute tubulointerstitial nephritis and uveitis. It poses diagnostic challenges due to the mostly asynchronous onset of renal and ocular manifestations, as well as the variety of differential diagnoses. This review provides an overview of the epidemiology, pathogenesis, clinical features, diagnostic criteria, and management strategies. Methods: A comprehensive review of the peer-reviewed literature, including studies and case reports, was conducted. Results: The etiology of TINU syndrome involves an autoimmune reaction to renal and ocular antigens, leading to interstitial inflammation and tubular damage in the kidneys, and anterior uveitis with acute onset of flares. Diagnostic criteria based on ocular examination, laboratory parameters, and renal biopsy emphasize the need to exclude other systemic diseases. TINU syndrome accounts for approximately 2% of all uveitis cases. Primary treatment consists of corticosteroids, while immunomodulatory therapies (methotrexate, azathioprine, mycophenolate mofetil, or biologic agents) are reserved for refractory cases. Recurrence of uveitis appears to be more common than that of nephritis. Conclusions: TINU syndrome is rare and requires clinical suspicion for accurate diagnosis. Early diagnosis and initiation of treatment are crucial for achieving favorable outcomes. Advances in the understanding of its pathogenesis and treatment have improved patient outcomes. Further research is needed to investigate the underlying triggers and mechanisms in order to develop targeted therapies.